Investigation of the influence of training status on the relationship between the acute exercise and serum leptin levels in obese females - Ozcelik, O; Celik, H; Ayar, A; Serhatlioglu, S; Kelestimur, H (Maghira & Maas Publications, 2004)
OBJECTIVE: Recent studies have concluded that an energy expenditure by an acute exercise session has no immediate effect on leptin levels while some showed a decline in leptin levels. The purpose of this study was to investigate any possible effects of training status of the subjects on acute exercise-leptin relationship in obese patients. MATERIALS AND METHODS: Fourteen obese sedentary females were enrolled to the study and effects of acute incremental exercise on serum leptin levels were determined at rest and at maximal exercise performance. Then, they participated to a 12-weeks endurance aerobic training programme performed in the laboratory on a computer controlled cycle ergometer and their leptin levels were re-evaluated and the leptin-acute exercise relationships obtained under different training levels in the same group of subjects were compared. The body compositions were determined by bioelectrical impedance. Pre and post training blood samples were taken at rest and at the maximal exercise performance. Serum leptin levels were analysed in duplicate by RIA. Data were evaluated using, paired t and Pearson's tests. RESULTS: Leptin levels were not acutely affected by the incremental exercise either before (23.62 +/- 3.5 ng/ml and 22.62 +/- 3.6 ng/ml) or after (13.13 +/- 3.4 ng/ml and 13.82 +/- 3.6 ng/ml) endurance training. The marked decrease in leptin levels following training was closely correlated with fat mass loss R = 0.899 (P = 0.0001). CONCLUSIONS: This study indicates that an increase in energy expenditure by acute exercise has no significant acute effect on leptin level regardless of the training status of the subjects and decrease in leptin levels after a 12-weeks endurance aerobic training programme are closely associated with the fat mass loss.
Keywords: leptin; acute exercise; obesity; weight loss; training